Young athletes cleared for sports participation after anterior cruciate ligament reconstruction: How many actually meet recommended return-to-sport criterion cutoffs? - Toole, A. R.; Ithurburn, M. P.; Rauh, M. J.; Hewett, T. E.; Paterno, M. V.; Schmitt, L. C. (Journal of Orthopaedic & Sports Physical Therapy, 2017)
Study Design: Prospective cohort study. Background: While meeting objective criterion cutoffs is recommended prior to return to sports following anterior cruciate ligament (ACL) reconstruction, the number of young athletes who meet recommended cutoffs and the impact of cutoffs on longitudinal sports participation are unknown. Objectives: To test the hypothesis that a higher proportion of young athletes who meet recommended cutoffs will maintain the same level of sports participation over the year following return-to-sport clearance compared to those who do not meet recommended cutoffs. Methods: At the time of return-to-sport clearance, the International Knee Documentation Committee Subjective Knee Evaluation Form (IKDC), quadriceps and hamstring strength limb symmetry index (LSI), and single-leg hop test LSI were assessed. Proportions of participants who met individual (IKDC score of 90 or greater; strength and hop test LSIs of 90% or greater) and combined cutoffs were calculated. Proportions of participants who continued at the same level of sports participation over the year following return-to-sport clearance (assessed using the Tegner activity scale) were compared between those who met and did not meet cutoffs. Results: Participants included 115 young athletes (88 female). The proportions meeting individual cutoffs ranged from 43.5% to 78.3%. The proportions meeting cutoffs for all hop tests, all strength tests, and all combined measures were 53.0%, 27.8%, and 13.9%, respectively. A higher proportion of participants who met cutoffs for both strength tests maintained the same level of sports participation over the year following return-to-sport clearance than those who did not (81.3% versus 60.2%, P = .02). Conclusion: The proportions of young athletes after ACL reconstruction recently cleared for return to sports who met the combined criterion cutoffs were low. Those who met the criterion cutoffs for both strength tests maintained the same level of sports participation at higher proportions than those who did not.